(Computationally) designing out waste: Developing a computational design workflow for minimising construction and demolition waste in early-stage architectural design. (December 2021) - Haeusler, Matthias H; Gardner, Nicole; Yu, Daniel K; Oh, Claire; Huang, Blair
In the architecture, engineering and construction (AEC) industry, waste is oft framed as an economic problem typically addressed in a building's construction and demolition phase. Yet, architectural design decision-making can significantly determine construction waste outcomes. Following the logic of zero waste, this research addresses waste minimisation 'at the source'. By resituating the problem of construction waste within the architectural design process, the research explores waste as a data and informational problem in a design system. Accordingly, this article outlines the creation of an integrated computational design decision support waste tool that employs a novel data structure combining HTML-scraped material data and historic building information modelling (BIM) data to generate waste evaluations in a browser-based 3D modelling platform. Designing an accessible construction waste tool for use by architects and designers aims to heighten awareness of the waste implications of design decisions towards challenging the systems of consumption and production that generate construction and demolition waste.